Bone density in the loggerhead turtle: functional implications for stage specific aquatic habits. (10th October 2013) - Maffucci, F.; Annona, G.; de, P.; Bologna, M. A.; Meomartino, L.; Montesano, A.; Bentivegna, F.; Hochscheid, S.
Abstract Several studies investigated how changes in bone density are related to the evolution of complex buoyancy control systems in aquatic mammals. Very little is known on sea turtles, although this is one of the most ancient tetrapod groups that successfully colonized the marine environments. Here, we investigated for the first time the relationship between bone density and body size in the loggerhead turtle, Caretta caretta, with the aim to elucidate possible functional connections with the species' aquatic habits. Humeri were extracted from the carcasses of 72 loggerhead turtles ranging in size from 7 to 89 cm (males = 18, females = 44, unknown = 10). Whole bone density was determined by Archimedes' principle. Sexes exhibited comparable humerus densities (t‐value = 0.49, P > 0.05). Mean humerus density (1.33 g cm−3) was intermediate within the range reported for marine mammals and suggested no extreme specialization towards an either pelagic or benthic lifestyle. Turtle size and humerus density were significantly correlated (Pearson's correlation = 0.638, P < 0.01). Small juveniles had very light bones compared to adults in accordance with their stage specific pelagic diving and foraging behaviour.